Transdiagnostic psychopathology in the light of robust single‐trial event‐related potentials - Randau, Martin; Bach, Bo; Reinholt, Nina; Pernet, Cyril; Oranje, Bob; Rasmussen, Belinda S.; Arnfred, Sidse (Psychophysiology, 2024)
Recent evidence indicates that event‐related potentials (ERPs) as measured on the electroencephalogram (EEG) are more closely related to transdiagnostic, dimensional measures of psychopathology (TDP) than to diagnostic categories. A comprehensive examination of correlations between well‐studied ERPs and measures of TDP is called for. In this study, we recruited 50 patients with emotional disorders undergoing 14 weeks of transdiagnostic group psychotherapy as well as 37 healthy comparison subjects (HC) matched in age and sex. HCs were assessed once and patients three times throughout treatment (N = 172 data sets) with a battery of well‐studied ERPs and psychopathology measures consistent with the TDP framework The Hierarchical Taxonomy of Psychopathology (HiTOP). ERPs were quantified using robust single‐trial analysis (RSTA) methods and TDP correlations with linear regression models as implemented in the EEGLAB toolbox LIMO EEG. We found correlations at several levels of the HiTOP hierarchy. Among these, a reduced P3b was associated with the general p‐factor. A reduced error‐related negativity correlated strongly with worse symptomatology across the Internalizing spectrum. Increases in the correct‐related negativity correlated with symptoms loading unto the Distress subfactor in the HiTOP. The Flanker N2 was related to specific symptoms of Intrusive Cognitions and Traumatic Re‐experiencing and the mismatch negativity to maladaptive personality traits at the lowest levels of the HiTOP hierarchy. Our study highlights the advantages of RSTA methods and of using validated TDP constructs within a consistent framework. Future studies could utilize machine learning methods to predict TDP from a set of ERP features at the subject level. In this study, we conduct a comprehensive examination of the correlations between well‐studied event‐related potentials (ERPs) and measures of transdiagnostic psychopathology consistent with The Hierarchical Framework of Psychopathology (HiTOP). To quantify ERPs, we utilize robust single‐trial analysis methods. In our mixed sample of healthy comparison subjects and patients with emotional disorders undergoing psychotherapy, we find evidence of correlations between ERPs and symptom and personality trait measures at several levels of the HiTOP hierarchy.